FDZ Data Description: Commercial Real-Estate Data for Germany (RWI-GEO-REDC V4) - Commercial advertisements on the Internet Platform ImmoScout24 01/2010-06/2024 - Felix Heuer; Patrick Thiel (RWI - Leibniz-Institut für Wirtschaftsforschung, 2025)
The FDZ Ruhr provides a dataset on commercial real estate advertisements in Germany, drawing from information obtained from the internet platform ImmoScout24. The dataset encompasses a wide range of real estate types, including but not limited to offices, retail, and hotels. It is important to note that the data are available for scientific research purposes only. The provided dataset offers detailed regional information and a comprehensive set of characteristics. This data report offers a concise overview of the data, its limitations, and specific details. The data report is intended for (potential) users of the data as support for their data preparation. This data report refers to RWI-GEO-REDC V4, which covers data from 01/2010 to 06/2024. Note that the years 2021 and 2022 are currently not present in the data. – – Das FDZ Ruhr stellt einen Datensatz zu gewerblichen Immobilienanzeigen in Deutschland zur Verfügung, der auf Informationen der Internetplattform ImmoScout24 beruht. Der Datensatz umfasst ein breites Spektrum an Immobilienarten, unter anderem Büros, Einzelhandel und Hotels. Es ist wichtig zu beachten, dass die Daten nur für wissenschaftliche Forschungszwecke zur Verfügung stehen. Der bereitgestellte Datensatz bietet detaillierte regionale Informationen und einen umfassenden Satz von Merkmalen. Die vorliegende Datenbeschreibung bietet einen knappen Überblick über die Daten, ihre Grenzen und spezifische Details. Die Datenbeschreibung ist für (potentielle) Nutzer der Daten als Unterstützung für deren Datenaufbereitung gedacht. Diese Datenbeschreibung bezieht sich auf RWI-GEO-REDC V4, das Daten von Januar 2010 bis Juni 2024 umfasst.
Keywords: 330